TaÅ£wÃ®r MÃ£ddatin Nahwi al â€˜ArabÃ® min KhilÃ£li an NushÃ»sh al Qurâ€™Ã£nÃ®yah Litarqiyati MahÃ£rÃµtil Iâ€™rÃµb ladÃ£ ThullÃ£bi Maâ€™had al AÃ®mah al â€˜ÃƒlÃ® al IslÃ£mÃ® bi Malang: Development of Nahwu Material Using the Texts of Al-Qur’an to Improve I’rab Skills for Students of Ma’had ’Ali al-Aimmah Malang - Eltoukhi, Ahmed Mohamed; Yunus, Badruzzaman M.; Musthafa, Izzuddin; Bahruddin, Uril (OKARA: Jurnal Bahasa dan Sastra, 2022)
There are problems experienced by students in learning Arabic, especially Nahwu and I’rab skills. This study aims to (1) develop Nahwu material using Qur’anic texts to improve the I’rab skills of students of Ma’had al-Aimmah al-â€˜Ali Malang, (2) determine the feasibility of the developed Arabic Nahwu material, and (3) measure the effectiveness of the application of the developed material. This study was research and development and analyzed using the five steps of ADDIE; analysis, design, development, implementation, and evaluation. Qualitative data were collected by interview, observation, and documentation, while quantitative data was collected using a questionnaire. The results of this study were 1) Nahwu material was developed based on the analysis of student needs to relate Nahwu material to the Qur’anic text. The material was designed using several selected Qur’anic texts, consisting of ten lessons. Each lesson came with objectives, content, exercises, and evaluations. The product was evaluated twice, before and after application. 2) The material developed is valid for testing, according to experts’ evaluation of the material categorized as very good. 3) After the material was tested on students, it was effective in improving I’rab skills. Finally, the Arabic Nahwu materials development through the Qur’anic texts achieved the outstanding results obtained by students through the application of the developed materials, namely: improvement of I’rab skills, ease of memorizing the Qur’an, and language understanding.